Computational modelling of adsorption and diffusion properties of CO2 and CH4 in ZIF-8 for gas separation applications: a density functional theory approach. Issue 6 (1st February 2021) - Paudel, Hari P.; Shi, Wei; Hopkinson, David; Steckel, Janice A.; Duan, Yuhua
Abstract : Understanding of zeolitic imidazolate framework-8 (ZIF-8) interaction with different gas molecules is crucial when ZIF-8 is used in gas separation. Abstract : Understanding of zeolitic imidazolate framework-8 (ZIF-8) interaction with different gas molecules is crucial when ZIF-8 is used in gas separation. Computational studies based on density functional theory (DFT) can be used to investigate gas interactions and diffusion mechanisms that can be directly correlated with experimental observations. Here we present our studies based on DFT calculations on CO2 and CH4 gas adsorption and diffusion in the bulk of ZIF-8. We evaluate the structural and electronic properties of bulk ZIF-8, and determine the most stable adsorption sites and the corresponding diffusion barriers for CO2 and CH4 molecules. Our calculations incorporate long-range dispersion interactions to describe the weak interactions between adsorbate molecules and the framework. We analyze the adsorption and diffusion properties in relation with the material's volume expansion. We find that the CO2 and CH4 adsorption energies at the most stable adsorption sites are 5.01 and 4.47 kcal mol −1, respectively. The diffusivity of CO2 is found to be about two times that of CH4 . Our calculated diffusion coefficients were found to have the same order of magnitude with the experimental results. Furthermore, our calculations indicate that CO2 and CH4 diffusivities in fixed ZIF-8 (all ZIF-8 framework atoms are fixed) are 5–9 times lower than the corresponding diffusion values in flexible ZIF-8 (all the framework atoms are allowed to move).